2019
DOI: 10.1101/720946
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vimentin provides the mechanical resilience required for amoeboid migration and protection of the nucleus

Abstract: statement (short abstract 40 words):Vimentinin joint action with actinmediates the mechanical stiffness of cells required for amoeboid cell migration through confined spaces and protects the nucleus from DNA damage. AbstractDendritic cells use amoeboid migration through constricted passages to reach the lymph nodes, and this homing function is crucial for immune responses. Amoeboid migration requires mechanical resilience, however, the underlying molecular mechanisms for this type of migration remain unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…Due to the numerous roles of vimentin, the effect of vimentin inhibition in non-malignant cells should be considered. To this end, consequences of its inhibition should be studied in animal models and effects on processes entailing cell migration (such as wound healing [73,133] or immune response [87,134]) should be carefully examined. However, since mice lacking vimentin develop and reproduce without any major problem [135], we can anticipate that beneficial vimentin inhibition in malignant cells outweighs any potential adverse effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the numerous roles of vimentin, the effect of vimentin inhibition in non-malignant cells should be considered. To this end, consequences of its inhibition should be studied in animal models and effects on processes entailing cell migration (such as wound healing [73,133] or immune response [87,134]) should be carefully examined. However, since mice lacking vimentin develop and reproduce without any major problem [135], we can anticipate that beneficial vimentin inhibition in malignant cells outweighs any potential adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that vimentin regulates nuclear shape and volume and protects the nucleus from DNA damage during invasion in confined environments. In amoeboid dendritic cells, vimentin IFs along with actin filaments were necessary for protection of the nucleus during confined migration, and loss of vimentin resulted in defective migration [87]. However, in mouse embryonic fibroblasts, the absence of vimentin IFs promoted migration through small pores [88].…”
Section: Vimentin and The Mechanics Of 3d Invasionmentioning
confidence: 99%
“…Vimentin may be particularly important for protecting the nucleus from compressive force, as several adaptor proteins have been reported to connect it to the nuclear envelope (25)(26)(27). Accordingly, Vimentin has been recently reported to protect the nucleus from rupture and DNA damage in confinement (28,29). In line with these results, we find the nucleus in Vimentin RNAi cells to undergo dramatic shape changes during LBBM.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that vimentin regulates nuclear shape and volume and protects the nucleus from DNA damage during invasion in confined environments. In amoeboid dendritic cells, vimentin IFs along with actin filaments were necessary for protection of the nucleus during confined migration, and loss of vimentin resulted in defective migration [86]. However, in mouse embryonic fibroblasts, the absence of vimentin IFs promoted migration through small pores [87].…”
Section: Vimentin and The Mechanics Of 3d Invasionmentioning
confidence: 99%